(untitled) (The East and Central African Journal of Pharmaceutical Sciences, 2018)
The gastrointestinal tract is chiefly involved in the digestion of ingested food, facilitation of absorption process and expulsion of the undigested food material through motility process. Motility is influenced by neurohormonal system which is associated with the enteric nervous system , autonomic nervous system and the higher centres in the brain. Many GIT diseases are characterized by altered function of the neurohormonal system associated with it, leading to various functional disorders. Characterization of various physiological factors involved in motility may lead to the development of specific drugs which may either enhance or decrease motility in various pathological conditions. A number of clinically used drugs including metoclopromide, cisapride and domperidone alter gastrointestinal motility via the modification of neurohormonal system. Targets need to be identified in several places in the enteric nervous system to normalize the deranged activity of gastrointestinal tract. The ultimate goal in managing patients with gastrointestinal disorders is to relieve symptoms and thereby improve the quality of life. In this review article, an exhaustive literature search was carried out to reveal the potential of important physiological systems that regulate gastrointestinal motility.